Double the Trouble When Herpesviruses Join Hands - Choi, Un Yung (Cell Host Microbe, 2017)
KSHV is the etiologic agent of PEL—an aggressive lymphoma. Interestingly, EBV concurrently exists in nearly 70% of PEL cases. In this issue of Cell Host & Microbe, McHugh et al. (2017) develop humanized mouse models for EBV/KSHV co-infection and identify their complementary effect on in vivo tumor formation.